The tachyon does matter - Buchel, Alex; Walcher, Johannes (Fortschritte der Physik, 2003)
We review the concept of S-branes introduced by Gutperle and Strominger [1]. Using the effective spacetime description of the rolling tachyon worldsheets discussed by Sen, we analyze the possibility that the gravitational backreaction of tachyon matter is important in the time-dependent process. We show that this is indeed the case in the example of the S0-brane in 4-dimensional Einstein-Maxwell theory. This talk is based on [21].
Gesehen am 15.02.2018